2013
DOI: 10.1007/s12544-013-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

Citation counts in transportation research

Abstract: Purpose In addition to the number of published articles, citation counts are traditionally interpreted as measures of publication merit. They are therefore used to evaluate researchers, research departments, universities and journals. Building on research conducted in scientometrics, we employ data from research articles in transportation research to investigate the influence on article citation counts of article and author characteristics in that particular field of research. Method and results Using standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The positive correlation between citation count and reference count is consistent to many previous studies (Peters and Van Raan, 1994 ; Lokker et al, 2008 ; Farshad et al, 2013 ; Hanssen and Jørgensen, 2014 ; Fox et al, 2016 ). However, the Pearson correlation coefficient was very small (0.289).…”
Section: Discussionsupporting
confidence: 91%
“…The positive correlation between citation count and reference count is consistent to many previous studies (Peters and Van Raan, 1994 ; Lokker et al, 2008 ; Farshad et al, 2013 ; Hanssen and Jørgensen, 2014 ; Fox et al, 2016 ). However, the Pearson correlation coefficient was very small (0.289).…”
Section: Discussionsupporting
confidence: 91%
“…For example, Sin (2011) showed that citation was higher for papers written through international collaboration, Northern European authors, and authors in high-income nations. Similar findings have been made by Aksnes (2003), Hanssen and Jørgensen (2014) and Katz and Hicks (1997).…”
Section: Background and Research Hypotheses Academic Collaboration Ansupporting
confidence: 90%
“…It had been suggested that citations could be higher for papers with international collaboration due to increased visibility of the papers as researchers from different countries may attract readers from different networks (Glänzel 2001;Hanssen and Jørgensen 2014;Hara et al 2003). On the other hand, due to transaction costs of collaboration, authors would only collaborate if the inherent quality of the work (articles) could be improved (e.g., using data from different sources or replicating studies in different countries to test robustness of the results).…”
Section: Background and Research Hypotheses Academic Collaboration Anmentioning
confidence: 99%
“…That more cited references correlate with higher citation rates was one of the outcomes in a study by Yu, Yu, Li, and Wang (), where library and information science was the field of interest. The same observation was made by Bornmann, Leydesdorff, and Wang (), in a study where the WoS subject categories were utilized for obtaining reference sets, as well as by Hanssen and Jorgensen, (), in a study on citation rates in transportation research.…”
Section: Earlier Studies Relevant To the Relationship Between Propertmentioning
confidence: 52%